Migrant Communities at the Center in Co-design of Health Literacy-Based Innovative Solutions for Non-communicable Diseases Prevention and Risk Reduction: Application of the OPtimising HEalth LIteracy and Access (Ophelia) Process - Dias, Sónia; Gama, Ana; Maia, Ana Catarina; Marques, Maria J.; Campos Fernandes, Adalberto; Goes, Ana Rita; Loureiro, Isabel; Osborne, Richard H. (Frontiers in Public Health, 2021)
The drivers of high prevalence of non-communicable diseases (NCD) among migrants are well-documented. Health literacy is regarded as a potential tool to reduce health inequalities and improve migrant's access to and quality of health care. Yet, little is known about the health literacy needs among these groups and how to address them. This paper outlines the protocol for a migrant community-based co-design project that seeks to optimize health literacy, health promotion, and social cohesion in support of prevention of NCDs among migrants in Lisbon using the OPtismizing HEalth LIteracy and Access (Ophelia) process. This participatory implementation research project starts with a mixed-methods needs assessment covering health literacy strengths, weaknesses and needs of migrants, and local data about determinants of health behaviors, service engagement, and organizational responsiveness. Diverse migrant groups will be engaged and surveyed using the Health Literacy Questionnaire and questions on sociodemographic and economic characteristics, health status, use of health services, and perceived impact of the COVID-19 pandemic. Semi-structured interviews with migrants will also be conducted. Based on data collected, vignettes will be developed representing typical persons with diverse health literacy profiles. Migrants and stakeholders will participate in ideas generation workshops for depth co-creation discussions in simulated real-world situations based on the vignettes, to design health literacy-based multisectoral interventions. Selected interventions will be piloted through quality improvement cycles to ensure ongoing local refinements and ownership development. Through a genuine engagement, the project will evaluate the uptake, effectiveness and sustainability of the interventions. This protocol takes a grounded approach to produce evidence on real health literacy needs from the perspective of key stakeholders, especially migrants, and embodies strong potential for effective knowledge translation into innovative, locally relevant, culturally and context congruent solutions for prevention of NCDs among migrants. Given the diverse communities engaged, this protocol will likely be adaptable to other migrant groups in a wide range of contexts, particularly in European countries. The scale-up of interventions to similar contexts and populations will provide much needed evidence on how health literacy interventions can be developed and applied to reduce health inequality and improve health in diverse communities.